EP828 Whole genome sequencing and clinical drug response data of 142 ovarian cancer samples. (1st November 2019) - de Witte, CJ; Kutzera, J; Espejo Valle-Inclan, J; van Roosmalen, MJ; Boymans, S; Cuppen, E; Kloosterman, WP; Zweemer, RP; Witteveen, PO; ,
Abstract : Introduction/Background: While most patients with ovarian cancer are initially sensitive to chemotherapy, approximately 75% will develop recurrent disease and become resistant. Predicted response to platinum is considered important in deciding on the best treatment upon recurrence. Often a disease-free interval of 6 months is considered the threshold between predicted resistance and sensitivity. In this study we compare clinical response to predicted response, and aim to identify mechanisms of chemotherapy resistance through whole genome sequencing (WGS) of matched pre-treatment biopsies. Methodology: Tissue biopsies were obtained in patients with advanced or metastatic ovarian carcinoma. Samples with minimally 30% tumour purity were characterized by WGS to a coverage of ∼100X (and 35X for corresponding germline samples). Predicted response to platinum, based on disease-free interval (6-month threshold) was compared to clinical response as measured according to the RECIST criteria on CT imaging. Results: In total, 137 patients were included and 142 ovarian cancer tissue biopsy samples were obtained, mainly of recurrent disease (111/142, 78%). Up to now, in 49 cases platinum (combination) treatment was given and response was assessed. Predicted response only correlated with measured response in 51% of patients. In the predicted sensitive group 11/29 patients (38%) were sensitive and experienced partial or complete response. In the group with predicted resistance 14/20 patients (70%) had progressive or stable disease. WGS data is being analysed to identify better prognostic criteria. Furthermore, we have started analysing copy number variation profiles of five patients for whom two subsequent biopsies were available. Evolution over time at copy number level did not seem to result from prolonged biopsy intervals or differences in tumour purity, but could be related to the number of previous treatment cycles. Conclusion: WGS augmented with detailed clinical data can potentially increase knowledge on the development of resistance and aid clinical decision making. Disclosure: No competing interests. Applicable funding sources: KWF Kankerbestrijding (Dutch Cancer Society) - UU2015-7743 [de Witte, Witteveen, Zweemer, Kloosterman].